2011
DOI: 10.1063/1.3595682
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of hydrogenated silicene and germanene

Abstract: The electronic properties of hydrogenated silicene and germanene, so called silicane and germanane, respectively, are investigated using first-principles calculations based on density functional theory. Two different atomic configurations are found to be stable and energetically degenerate. Upon the adsorption of hydrogen, an energy gap opens in silicene and germanene. Their energy gaps are next computed using the HSE hybrid functional as well as the G0W0 many-body perturbation method. These materials are foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
318
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(340 citation statements)
references
References 22 publications
19
318
0
3
Order By: Relevance
“…Due to strong spin-orbit coupling (SOC), the quantum spin Hall effect may be observed in silicene in an experimentally accessible temperature regime [13]. A tunable band gap can be opened up to about 4 eV in silicene by applying a perpendicular electric field [21][22] and by hydrogenation [23][24][25][26], halogenation [27][28], and oxidation [29][30]. Owing to these excellent properties and easy integration into the current Si-based semiconductor technology, silicene holds great promise for future applications in nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Due to strong spin-orbit coupling (SOC), the quantum spin Hall effect may be observed in silicene in an experimentally accessible temperature regime [13]. A tunable band gap can be opened up to about 4 eV in silicene by applying a perpendicular electric field [21][22] and by hydrogenation [23][24][25][26], halogenation [27][28], and oxidation [29][30]. Owing to these excellent properties and easy integration into the current Si-based semiconductor technology, silicene holds great promise for future applications in nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous chemical methods, hydrogenation has been demonstrated to be one of the most powerful approaches to tune the electronic properties of 2D materials. For example, it has been demonstrated that hydrogenation can open sizable band gaps in graphene [40][41][42], graphyne [43], and single-layer silicene [44][45][46]. However, none of these hydrogenated structures reported to date is suitable for solar applications; in particular, there may be a strong phase separation in the ground states of these materials.…”
mentioning
confidence: 99%
“…In the so-called boat configuration the H atoms alternate in pairs instead, which slightly increases the unit cell size. The latter has been shown to be notably less stable than the chair configuration in the case of graphane [29], nevertheless the boat configuration of silicane and germanane has been found to be stable [25] which is important to bear in mind.…”
mentioning
confidence: 99%